2020
DOI: 10.1101/2020.09.05.284182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying mechanical loading and elastic strain energy of the human Achilles tendon during walking and running

Abstract: The purpose of the current study was to assess Achilles tendon (AT) mechanical loading and strain energy during locomotion using a new in vivo approach for measuring AT length that considers the AT curve-path shape. Eleven participants walked at 1.4 m/s and ran at 2.5 m/s and 3.5 m/s on a treadmill. AT length, defined as the distance between its origin at the gastrocnemius medialis myotendinous junction (MTJ) and the calcaneal insertion, was determined experimentally by integrating kinematics and ultrasound an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Finally, because previous studies of how AT moment arm length influences COL have used trained runners running on a treadmill at a speed of 16 km/h, it is still unknown how variation in speed and athletic training impacts elastic loading to the tendon in relation to moment arm length. While previous work has explored elastic loading of the AT at different speeds and under different loading conditions 10 21 , this study is the first to investigate the potential correlation between foot geometry like the AT moment arm length and spring-like behavior of this tendon in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, because previous studies of how AT moment arm length influences COL have used trained runners running on a treadmill at a speed of 16 km/h, it is still unknown how variation in speed and athletic training impacts elastic loading to the tendon in relation to moment arm length. While previous work has explored elastic loading of the AT at different speeds and under different loading conditions 10 21 , this study is the first to investigate the potential correlation between foot geometry like the AT moment arm length and spring-like behavior of this tendon in humans.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study mimicking the patellar tendon force by applying the peak muscle activity in the vasti muscles, demonstrated a similar pattern, although the muscle activity decreased from 18.6 km/h to 25 km/h [26]. Moreover, using a force transducer on the Achilles tendon, Kharazi et al [27] demonstrated that the Achilles tendon peak force grows linearly from 5-12.6 km/h. With a similar method, Komi [28] demonstrated that the Achilles tendon peak force was increasing until around 21 km/h (6 m/s) and thereafter decreasing at higher speeds.…”
Section: Comparing Structure Specific Forcesmentioning
confidence: 78%